KINETICS OF FELDSPAR AND QUARTZ DISSOLUTION AT 70-80°C AND NEAR-NEUTRAL PH: EFFECTS OF ORGANIC ACIDS AND NACL - EFFECTS OF PH, CO2, AND ORGANIC ACIDS - Blake R.E.; Walter L.M. (My University, 1999)
Effects of the organic acid (OA) anions, oxalate and citrate, on the solubility and dissolution kinetics of feldspars (labradorite, orthoclase, and albite) at 80°C and of quartz at 70°C were investigated at pH 6 in separate batch experiments and in media with different ionic strength (0.02-2.2 M NaCl). Although it has been shown that OAs can increase rates of feldspar dissolution, prior experiments have focused primarily on dilute, highly undersaturated and acidic conditions where feldspar dissolution kinetics are dominated by H+ adsorption and exchange reactions. Many natural waters, however, are only weakly acidic and have variable ionic strength and composition which would be expected to influence mineral surface properties and mechanisms of organic ligand-promoted reactions.Oxalate and citrate (2-20 mM) increased the rate of quartz dissolution by up to a factor of 2.5. Quartz solubility, however, was not increased appreciably by these OAs, suggesting that Si-OA complexation is not significant under these conditions. The lack of significant OA-SiO2 interaction is important to understanding the effects of OAs on the release of both Si and Al from feldspars. In contrast to quartz, both the rates of dissolution and amounts of Si and Al released from the three feldspars studied increased regularly with increasing OA concentration. Feldspar dissolution was congruent at all but the lowest OA concentrations. Total dissolved Al concentrations increased by 1-2 orders of magnitude in the presence of oxalate and citrate, and reached values as high as 43 mg/l (1.6 mM). Si concentrations reached values up to 65 mg/l (2.3 mM) in feldspar-OA experiments. Precipitation of authigenic clays was observed only in experiments without or at very low concentrations of OAs. The high concentrations of dissolved Si attained during dissolution of feldspars in OA solutions, relative to Si concentrations in quartz-OA experiments, is attributed to concomitant release of Si driven by strong Al-OA interactions.Modeling of the dependence of feldspar dissolution rates on OA concentration in natural diagenetic environments is complicated by the competing effects of overall solution chemistry and ionic strength on the dissolution mechanism. Results of experiments using labradorite (An70) indicate that in OA-free solutions, dissolution is progressively slower at increasing NaCl concentrations (up to 2.2 M), in agreement with prior experiments on the effects of alkali metals on feldspar dissolution. The combined effects of oxalate and NaCl on labradorite dissolution rates are such that the rate increase due to oxalate is suppressed by the addition of NaCl. Thus, feldspar dissolution kinetics should be most significantly affected by a given concentration of OAs in low ionic strength solutions.